Fakhr AL-DĪN AL-RĀZĪ’S Critique of Avicennian Psychology and the Transcendental Individuation of Human Souls - M. Fakhuruddin Attar (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This article examines the psychological doctrines of the AshÊ¿arite theologian and polymath Fakhr al-DÄ«n al-RÄzÄ« (d. 606/1210). The starting point of the discussion is his critical reception of Avicennaâ€™s (d. ca. 428/1037) psychological theories. I focus on al-RÄzÄ«â€™s early works on philosophy, in particular al-MabÄá¸¥ith al-mashriqiyya and his famous commentary on Avicennaâ€™s al-IshÄrÄt wa-l-tanbÄ«hÄt. I show that RÄzÄ« affirms a theory of the human soul that is heavily influenced by his predecessor. However, I also show that offers a distinct perspective on fundamental issues. I offer a detailed discussion of two RÄzian psychological doctrines: that human souls are heterogenous, rather than constituting a single species â€œrational animalâ€ pace Avicenna; and that they are caused by celestial entities called Perfect Natures, a theory that is adopted from the practitioners of talismanic magic. The resulting cosmological theory can be referred to as the transcendental individuation of human souls